Proposed implementation of a checklist for recruitment patterns of short selection of small claims in procurement manual ministry of national defense (2013)
Accordingly to the changes in the norms and management laws, during the last 30 years, The Colombian Public Administration, has structured its procedures between the public offices contracting with juridical or natural persons from the public or private sector, to accomplish all the obligations and needs; this was made to guarantee the principles of state contraction and how the state manage the public resources.